2014
DOI: 10.7287/peerj.preprints.476v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in healthcare expenditures for inflammatory bowel disease by insurance status, income, and clinical care setting

Abstract: View the peer-reviewed version (peerj.com/articles/587), which is the preferred citable publication unless you specifically need to cite this preprint. expenditures for CD, UC, and all IBD were $10,364 (N=238), $7,827 (N=95), and $9,528, respectively, significantly higher than non-IBD ($4,314, N=276,372, p<0.05). Publicly insured patients incurred the highest costs ($18,067), over privately insured ($8,014, p<0.05) or uninsured patients ($5,129, p<0.05). Among all IBD patients, inpatient care composed the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…7 It also reports total expenditures per patient per year as $12,542 which was lower compared to previous estimates of $17,500 4 to $24,500 5 ; and higher compared to a previous estimate of $10,364. 20 Further, in the differencein-differences estimations, total and prescription expenditures in respondents with Crohn's disease had a higher increase compared to respondents without Crohn's disease pre-post FDA approvals of new biologics and the American College of Gastroenterology Crohn's disease treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It also reports total expenditures per patient per year as $12,542 which was lower compared to previous estimates of $17,500 4 to $24,500 5 ; and higher compared to a previous estimate of $10,364. 20 Further, in the differencein-differences estimations, total and prescription expenditures in respondents with Crohn's disease had a higher increase compared to respondents without Crohn's disease pre-post FDA approvals of new biologics and the American College of Gastroenterology Crohn's disease treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Park and colleagues reported that inpatient expenditures represented a large proportion of total expenditures (36%) compared to prescriptions (8%) using MEPS data spanning from 1996 to 2011. 20 Similarly, Gibson and colleagues reported that inpatient expenditures represented 46% of total expenditures while prescription expenditures only represented 12%. 6 This appears reasonable given that costs may have shifted from inpatient to prescription expenditures due to the introduction of biologics in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence for IBD has been increasing in recent years, about 1.2–1.6 million affected patients . The annual direct expenditure for IBD is about $6.7 billion, making the annual cost per patient about $10 000 for CD and $7500 for UC . Additionally, the indirect IBD cost (employee absenteeism) were estimated to be about $249 million in United States (2006's value) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified several factors that associated with higher expenditure in IBD. These factors include age, insurance status, income, body mass index (BMI), gender, race, smoking status and education . However, these studies used different population groups.…”
Section: Introductionmentioning
confidence: 99%